Examining mediating effect of entrepreneurship on microfinance and economic development - Alshammari, Ahmed Mahmoud Abdallah
Jordan has witnessed prorrusing blooming economy over the past few decades. Nevertheless, many issues faced by its economy such as the large increase in poverty, lack of employment opportunities, low standard of living, weak infrastructure, and slow progress in various social and economic indicators. The government has implemented some policies, but unfortunately, most of them failed due to poor implementation in Jordan. This study explored the relationship between microfinance and economic development through entrepreneurship and the impact of its relationship. The study examined the relationship between entrepreneurial variables as an intermediary between microfinance and economic development. This study employed quantitative method in data collection process. A self-administered questionnaire was used to collect data after validating the questionnaires by the pilot test. The sample size used in this study was 330 employees from the entrepreneurial sector who were under the microfinance institutions sector in Jordan, and these institutions were listed and offici all approved by Central Bank of Jordan. A total of 330 questionnaires were distributed to employees, completed questionnaires were collected and there were 320 questionnaires that were valid for further analysis. The framework of the study was tested using multiple regression analyses to prove the hypotheses that were developed for the study using the modelling of the Partial Least Squares Structural Equation Modelling (PLS-SEM). The results showed that microfinance has a significant positive effect on economic development in Jordan. In addition, the result revealed that microfinance and entrepreneurship have significant positive relationship, entrepreneurship and economic development also revealed a significant positive relationship between them. Finally, the results indicated that entrepreneurship have full mediation effect on microfinance and economic development in Jordan. The results of this study contributed to the theoretical, methodological and practical possibilities and opened the door for further research. The study provided empirical insights in supporting the theory that entrepreneurship should be used in microfinance.